(untitled) (Revista Ciência Agronômica, 2017)
This study aimed to evaluate biochemical changes in seeds of the pumpkin hybrid, ‘Jabras’, from fruit harvested at different stages of maturation (15, 30, 45, 60 and 75 days after anthesis). Thirty fruit were harvested at each stage, with the seeds from 15 of the fruit being extracted immediately. The remaining 15 were stored for twenty days in plastic boxes and the seeds extracted after this period. After processing and drying the seeds, the following were determined: moisture content, germination, first count and antioxidant enzyme activity (peroxidase, ascorbate peroxidase, catalase and superoxide dismutase). Seeds from the fruit harvested at 30 DAA displayed low values for germination and vigour and high antioxidant enzyme activity, indicating that they were immature and that drying possibly caused damage to the system of cell membranes. The results obtained in this study demonstrated that analysis related to changes in the activity of enzymes during development and maturation of the seeds was effective in evaluating the physiological and biochemical changes in pumpkin seeds of the ‘Jabras’ cultivar.